Predictors of Brain Natriuretic Peptide Serum Level Elevation in Patients with Symptomatic Chronic Subdural Hematoma: A Prospective Study - Chihi, Mehdi (J Clin Med, 2021)
Background: Brain natriuretic peptide serum levels (BNP) on admission are frequently elevated in patients with symptomatic chronic subdural hematoma (cSDH) and predict unfavorable long-term functional outcomes. However, the reasons for these elevated levels remain unclear. Therefore, we aimed to identify the predictors of BNP elevation. Methods: Patients with unilateral symptomatic cSDH who were surgically treated in our department between November 2016 and May 2020 were enrolled. Patients’ symptoms and neurological deficits were prospectively assessed using a study questionnaire. On initial computer tomography, hematoma volumes and midline shift (MLS) values were measured to analyze the degree of brain compression. Results: In total, 100 patients were analyzed. Linear regression analysis showed that higher BNP levels were significantly associated with smaller hematoma volumes (p = 0.003) and littler MLS values (p = 0.022). Multivariate analysis revealed that presence of a neurological deficit (p = 0.041), a hematoma volume < 140 mL (p = 0.047), advanced age (p = 0.023), and head trauma within 24 h of admission (p = 0.001) were independent predictors of BNP elevation. Conclusion: In symptomatic cSDH, BNP elevation is related, among others, to the presence of neurological deficits and smaller hematoma volumes. Whether BNP elevation may coincide with the early stage of hematoma growth, i.e., immaturity of cSDH neomembrane, requires further investigations.